2012
DOI: 10.1038/aja.2012.121
|View full text |Cite
|
Sign up to set email alerts
|

Environmental mercury exposure, semen quality and reproductive hormones in Greenlandic Inuit and European men: a cross-sectional study

Abstract: Several animal studies indicate that mercury is a male reproductive toxicant, but human studies are few and contradictory. We examined semen characteristics and serum levels of reproductive hormones in relation to environmental exposure to mercury. Blood and semen samples were collected from 529 male partners of pregnant women living in Greenland, Poland and Ukraine between May 2002 and February 2004. The median concentration of the total content of mercury in whole blood was 9.2 ng ml 21 in Greenland (0.2-385… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 52 publications
(91 reference statements)
1
26
0
2
Order By: Relevance
“…We also confirm a previously reported strong positive association between mercury and inhibin B 40. As inhibin B, predominantly excreted by Sertoli cells, is correlated with sperm concentration and counts and serves as a marker of spermatogenesis,44 this positive association is contrary to a deleterious effect of exposure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also confirm a previously reported strong positive association between mercury and inhibin B 40. As inhibin B, predominantly excreted by Sertoli cells, is correlated with sperm concentration and counts and serves as a marker of spermatogenesis,44 this positive association is contrary to a deleterious effect of exposure.…”
Section: Discussionsupporting
confidence: 90%
“…As inhibin B, predominantly excreted by Sertoli cells, is correlated with sperm concentration and counts and serves as a marker of spermatogenesis,44 this positive association is contrary to a deleterious effect of exposure. The authors40 suggest that this association may be driven by a higher consumption of seafood—particularly relevant for Greenlandic Inuit—and the resultant concomitant exposure to mercury and ω-3 polyunsaturated fatty acids. There are indications that the latter may beneficially impact certain semen quality parameters 45.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Hg binds to the estrogen receptor and impairs the action of E 2 (Tilghman et al 2008). Mocevic et al (2013) studied men coming from the area of Greenland, Poland and Ukraine, and found no relationship between wholeblood Hg and follicle-stimulating hormone (FSH), luteinizing hormone (LH), TT and FAI, although they did not determine E 2 levels. Rambousková et al (2014) studying the concentration of Hg in the blood of people at geriatric age showed a negative correlation between Hg and age.…”
Section: Metalsmentioning
confidence: 98%
“…The main results of relevant studies are shown in Table 1. However, some groups have found no influence of Pb, Cd, or Hg on sperm (Noack-Füller et al, 1993;Kasperczyk et al, 2002;Bonde et al, 2002;Mocevic et al, 2013).…”
Section: Direct Mechanism Of Spermatogenesis Alterationsmentioning
confidence: 95%